Hubungan Stimulasi Bermain, Faktor Keluarga dan Faktor Anak dengan Perkembangan Balita di Wilayah Kerja Puskesmas Aur Duri Kota Jambi - Gusti Lestari Handayani; Abbasiah Abbasiah (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The development of technology and the era of globalization affect many things, including the type of children's play, which is one of the factors that influence children's development. Children's development is also influenced by stimulation and psychological. Stimulation, especially in the family, for example by providing toys, child socialization, involvement of mothers and other family members will influence the child in achieving optimal development. Early age problems that are not resolved from the beginning can lead to developmental problems in the future, the effect not only on the person concerned but on the environment. The purpose of this study was to determine the relationship of play stimulation, parent factors and child factors with the development of children under five in the Puskesmas Aurduri, Jambi City. The study design was cross sectional with a minimum sample size of 31 children with α = 0.05 and β = 10%. The research location is the Aur Duri Health Center Work Area Jambi City. The subject of the research was Toddler in the working area of Aurduri Public Health Center in Jambi City. The results showed there was a significant relationship between types of play stimulation (P value 0.035) and parenting (P value 0,000) with the development of toddlers. Attention needs to be paid to the provision of play equipment for children to suit the child's function and development. And Increase efforts to monitor the development of toddlers through routine detection of toddlers according to age.